Réponses

2013-12-06T01:04:12+01:00
Je vais essayer...
A = 2 -g² -5 +10g² - 2g + 6g
A= 2-5 -g²+10g² -2g+6g
A= -3 +9g² +4g

B= 6 -(-6c)   -(-10)   -10c   +9c²   -(-6c²)
B= 6 +6c +10 - 10c + 9c²  +6c²
B= 6 +10 +6c-10c +9c²+6c²
B= +16 -4c +15c²

C= 8 -(-8z²) -3z -10 -(-7z²) +3z
C= 8 +8z² -3z -10 +7z² +3z
C= +8-10 -3z+3z +8z²+7z²
C= -2 +15z²

Exo3

A=6x² -9 -(3x²)-(4x) -5x+1
A= 6x² -9 +3x² -4x -5x +1
A= -9 +1 -4x -5x +6x²+3x²
A= -8 -9x +9x²

B= -9 +5a² -a² -5a -(-6) -8a
B= -9 +5a² -a² -5a +6 -8a
B=-9+6 -5a-8a +5a²-a²
B= -3 - 13a +4a²

C= -1 -  +2h + 4h² - (-6) - 7h² -5h
C= -1 -  +2h + 4h² +6 - 7h² -5h
C= -1+6 +2h-5h +4h²-7h²
C= +5 -3h -3h²

J'espère ne pas m'être trompé dans les signes  !!!!!